The evolutionary thermal performance and development of a novel thermal diode pre-heat solar water heater under simulated heat flux conditions. (December 2017) - Smyth, M.; Quinlan, P.; Mondol, J.D.; Zacharopoulos, A.; McLarnon, D.; Pugsley, A.
Abstract: This paper presents the development through experimental performance characterisation of a pre-heat ICSSWH that utilises a novel thermal diode operation to reduce ambient heat loss during non-collection periods. Using a bespoke thermal flux simulation test facility, 4 prototype versions of the pre-heat thermal diode ICSSWH were produced and evaluated (Mark I to IV) at Ulster University. Each prototype was developed and evolved on the previous design, encompassing performance improvements and fabrication enhancements. The concept has been designed and developed to be a sustainable, pre-heat alternative to other solar water heating systems traditionally used in DHW installations in retro-fit and social housing applications. The highest 6 h and 3 h collection efficiency was 33.2% and 41.97%, respectively under thermally simulated conditions for a unit with capillary matting and 150 mbar internal pressure (MIIIb 17). The lowest system 'U' value was 0.98 W m −2 K −1 (long and thin raised pockets, MIV 12) under thermal (solar) flux simulation testing and no draw-off conditions. When the current prototype ICS units are compared with other conventional ICS systems, particularly in terms of thermal retention during non-collection periods, an improved performance is clearly demonstrated. The measured thermal losses were approximately 50% less than other similarly measured systems. Highlights: Experimental performance characterisation of a pre-heat ICSSWH. A novel thermal diode operation to reduce ambient heat loss during non-collection periods. Experimental evaluation via a bespoke thermal flux simulation test facility. 6 h collection efficiency of 33.2% and 3 h collection efficiency of 41.97%. System 'U' value was 0.98 W m −2 K −1 .